2019
DOI: 10.4172/2165-8048.1000300
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Adverse Birth Outcomes and Associated Factors among Diabetic Pregnant Mothers Who Delivered at Mettu Karl Hospital, Illubabor Zone, South West Ethiopia-2018

Abstract: Diabetes in pregnancy is the major cause of poor birth outcome that encountered during pregnancy. Worldwide, 7% of all pregnancies are complicated by diabetes and causes for maternal and prenatal morbidity and mortality. Objective: To assess birth outcomes and associated factors among diabetic pregnant mothers who delivered at MKH,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…From 7 studies four were done in Addis Ababa [19,[22][23][24], one in Amhara region [36], and the remaining two in Oromoia region [20,37]. All studies were conducted at different hospitals of Ethiopia using different study design; four cross-sectional [20,[22][23][24], two case-controls [36,38], and one prospective cohort [19]. This systematic review and metaanalysis also showed factors associated with adverse birth outcome among diabetes women.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…From 7 studies four were done in Addis Ababa [19,[22][23][24], one in Amhara region [36], and the remaining two in Oromoia region [20,37]. All studies were conducted at different hospitals of Ethiopia using different study design; four cross-sectional [20,[22][23][24], two case-controls [36,38], and one prospective cohort [19]. This systematic review and metaanalysis also showed factors associated with adverse birth outcome among diabetes women.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…A total of 7 studies with 1,225 study participants were included in this systematic review and meta- analysis. From 7 studies four were done in Addis Ababa [ 19 , 22 – 24 ], one in Amhara region [ 36 ], and the remaining two in Oromoia region [ 20 , 37 ]. All studies were conducted at different hospitals of Ethiopia using different study design; four cross-sectional [ 20 , 22 – 24 ], two case-controls [ 36 , 38 ], and one prospective cohort [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Elsewhere, two independent authors (DM and DK) evaluated the eligibility of all retrieved studies using the Joanna Briggs Institute (JBI) quality appraisal checklist ( 35 ). Hence, one prospective cohort study ( 18 ), four cross-sectional studies ( 19 21 ), and two case–control studies ( 23 , 36 ) were appraised for quality using the JBI checklist. Therefore, studies are considered high quality whenever they meet 50% and/or above quality assessment criteria.…”
Section: Methodsmentioning
confidence: 99%